2016
DOI: 10.3791/54275
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming in Older People Living with HIV Improves Balance, Mobility and Ameliorates Some Aspects of Frailty

Abstract: Approximately 1.2 million people in the United States live with HIV infection. Medical advancements have increased the life expectancy and this cohort is aging. HIV-positive individuals have a high incidence of frailty (~20%) characterized by depression and sedentary behavior. Exercise would be healthy, but due to the frail status of many HIV-positive individuals, conventional exercise is too taxing. The aim of this study was to evaluate the effectiveness and acceptability of a novel game-based training progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Our cutoff age was less than 65 years since we did not exclude those with chronic medical condition (e.g., diabetes mellitus, peripheral arterial disease, HIV, etc. ), in whom geriatric symptoms were reported at earlier age [ 44 , 45 , 46 ]. Exclusion criteria were sign of severe cognitive impairment, which was evaluated using Mini-Mental State Examination (MMSE) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our cutoff age was less than 65 years since we did not exclude those with chronic medical condition (e.g., diabetes mellitus, peripheral arterial disease, HIV, etc. ), in whom geriatric symptoms were reported at earlier age [ 44 , 45 , 46 ]. Exclusion criteria were sign of severe cognitive impairment, which was evaluated using Mini-Mental State Examination (MMSE) [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the Frailty Meter is easy to use, incorporating software that is intuitive, an improvement over the previous technology we used to measure frailty. 9…”
Section: Introductionmentioning
confidence: 99%
“…Of the eight studies that measured depression, five studies suggested that the interventions yielded significant improvement (p < 0.05), while no significant difference was reported in two studies (Ownby & Acevedo, 2016;Veeravelli et al, 2016), and one study measured depression at baseline only (Frain & Chen, 2018). Similarly, two studies suggested significant (p < 0.05) reduction in stressor burden among treatment participants compared to control group (Heckman et al, 2001(Heckman et al, , 2006.…”
Section: -10% Of Participants Status Deterioratedmentioning
confidence: 98%
“…Seven studies cited additional participant inclusion criteria, such as having some degree of depression or cognitive impairment. Sample sizes varied from 10 to 361, but most studies (n = 5) had small sample sizes of less than 25 (Brennan-Ing et al, 2017;Frain & Chen, 2018;Heckman et al, 2001;Ownby & Acevedo, 2016;Veeravelli et al, 2016). The average number of years living with HIV was reported in six studies and ranged from 8.5 years to 18.0 years (Heckman et al, 2001;Shah et al, 2016).…”
Section: Hivmentioning
confidence: 99%